KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN TELAGA SEGOAR, DESA BAYAN, KECAMATAN BAYAN, KABUPATEN LOMBOK UTARA - Nutrinem; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
This study aims to analyze the diversity of yard plant species in Telaga Segoar Hamlet, Bayan Village, Bayan District, North Lombok Regency. The method used was direct observation of community yards, then the data obtained were analyzed using the Shannon-Wiener diversity index (H’). The results showed that there were various types of plants. The diversity index value obtained was H’ = 1.94 which is included in the moderate diversity category. This indicates that the level of distribution of individuals between species is moderate and no species dominates extremely. In addition, this condition reflects the stability of the community which is at a moderate level, so that the yard ecosystem in the area is quite balanced but still requires sustainable management.